Aqua-rythmics : exercises for the swimming pool. - NolteHeuritsch Ilse (New York : Sterling Pub., 1978)
A series of well illustrated exercises to be used as a cure for overweight persons or anyone wishing to develop and retain a slim figure.
Keywords: Aquatic sports; Exercise for women